PREVALENCE OF DIABETES MELLITUS COMPLICATIONS IN ADOLESCENTS: A CROSS-SECTIONAL STUDY (Editora Impacto Científico, 2025)
Diabetes Mellitus, as a chronic condition with increasing incidence among adolescents, presents a high risk for complications that negatively impact quality of life, justifying the importance of investigating this condition within the scope of Primary Health Care. Therefore, the objective of this study was to analyze the prevalence of DM complications in adolescents followed by the Family Health Strategy in a municipality in the Macro-West Region of Minas Gerais. To this end, a descriptive cross-sectional study was conducted, developed from secondary data obtained from the Citizen's Electronic Health Record, between February and March 2024. Adolescents diagnosed with type 1 or type 2 DM were included, whose sociodemographic and clinical information was analyzed using descriptive statistics and the Chi-square test, adopting a significance level of p